IMPLEMENTASI PELAKSANAAN PROGRAM SKRINING HIPOTIROID KONGENITAL (SHK): LITERATURE REVIEW - Dumilah, Retno; Yulifah, Rita; Mansur, Herawati; Suprapti, Suprapti; Darwanty, Jundra (Media Penelitian dan Pengembangan Kesehatan, 2023)
Hypothyroidism has a major impact on cardiovascular, neurological, gastrointestinal function, metabolic function and growth disorders. Congenital Hypothyroidism Screening (SCH) is an effort to improve the quality of life and prevent growth and development disorders in toddlers. In implementing SHK, problems often arise, including a lack of retraining for health workers, a lack of an appropriate information technology system, a mix-up in the distribution of logistical needs, national health policy guarantees, applicable SOPs and patients who are less cooperative. The aim of this research is to study the implementation of The SHK program in various countries. The research used a literature review method, data sources were collected Through the PubMed database with the keywords Congenital Hypothyroidism. Inclusion criteria are research articles published in 2017-2023, using Indonesian and English, articles regarding the implementation of the SHK program and the research location has an SHK program. A total of 150 articles were collected, 8 articles were described. Results Most countries carry out SHK along with screening for other diseases in newborns. The success of SHK can extend The life expectancy of sufferers. Treatment side effect prevention programs are being developed in countries that have successfully implemented SHK.